Resource-constrained production scheduling problem with multi-robot task in smart factory using deep reinforcement learning - Phan, Toan Thanh; Nguyen, Tuan Anh; Vu, Thoai Minh (Vietnam Journal of Science and Technology, 2026)
Smart factories integrate diverse components such as humans, robots, artificial intelligence, cloud computing, and IoT systems, promising to enhance production efficiency, customization, and waste reduction to meet the demanding requirements of modern industry. A critical component is the Manufacturing Execution System (MES), which bridges the planning and production execution phases and performs functions including data collection, production coordination, equipment maintenance, detailed scheduling, resource allocation, and quality control. However, most current MES systems have not yet integrated resource scheduling capabilities, creating an urgent need for efficient scheduling algorithms that increase productivity, reduce workflow execution time, and optimize resource utilization. The core challenges involve multiple multi-stage tasks with complex constraints on completion time, system resources, and spatial positioning, including managing job allocation for multiple heterogeneous robots, coordinating resources to avoid delays from buffer limitations or bottlenecks, and optimizing execution time to prevent production-line stoppages. This research develops a machine learning model based on reinforcement learning to optimize resource-constrained production scheduling in smart factories, designated DRL-RCPSSP, focusing on improving performance, resource allocation, and adaptability under dynamic conditions.